A surface plasmon resonance fibre device for environmental sensing - Allsop, Thomas P.; Neal, Ron M.; Brown, Patrick R.; Saied, Sayah O.; Rehman, Saeed Ur; Kalli, Kyriacos; Webb, David J.; Sullivan, John L.; Mapps, Desmond J.; Bennion, Ian (My University, 2008)
We demonstrate a surface plasmon resonance sensor that operates in air and has index resolution ~10-4 in the 1 to 1.3 index range. The sensor comprises a multi-layered thin film on a D-shaped fibre.
Keywords: Fiber optics; Plasmons; Surface plasmon resonance